HUBUNGAN ANTARA INDEKS MASSA TUBUH DENGAN AGILITY DAN FLEXIBILITY PADA ANAK USIA 7-12 TAHUN - Nisa Anita Rahmalia (2023)
Background: Body mass index is one of the many types of measurements that are often used to measure body composition. Individuals with a good body mass index usually have good health and agility and flexibility as well. Several studies suggest a close relationship between body mass index and physical fitness such as the effect of BMI on agility and flexibility which are components of physical fitness. Purpose: The aim of this study was to determine the relationship between body mass index and agility and flexibility in children aged 7-12 years. Method: This research method is a correlation study using a cross sectional approach. A total of 111 students at SDN 2 Girijaya Garut participated in this study. The parameters used are tables from the National Center for Chronic Disease Prevention and Health Promotion to determine the level of body mass index in children, the Shuttle Run 4 x 10 m to measure agility and the Sit and Reach Test to measure flexibility. Results: Based on the Fisher's Exact Test analysis for body mass index and agility, the results obtained were p <0.000 or p <0.05 and for the relationship between body mass index and flexibility, the results obtained were p <0.000 or p <0.05. Conclusion: This study found a significant relationship between Body Mass Index and Agility and Flexibility in children aged 7-12 years.